The polypill in cardiovascular prevention: evidence, limitations and perspective – position paper of the European Society of Hypertension. Issue 8 (August 2017) - Coca, Antonio; Agabiti-Rosei, Enrico; Cifkova, Renata; Manolis, Athanasios J.; Redón, Josep; Mancia, Giuseppe
Abstract : N/A: Antihypertensive, lipid lowering, antidiabetic and antiplatelet treatments all substantially reduce the risk of cardiovascular morbid and fatal events. In real life, however, effective implementation of these treatments is rare, and thus their contribution to cardiovascular prevention is much less than it could be, based on research data. This article reviews the pros and cons of cardiovascular prevention by the polypill approach. It is argued that the high prevalence of individuals with a multifactorial risk profile provides a strong rationale for a therapeutic strategy based on the combination in a single tablet of drugs against different risk factors. It is further argued that other important favourable arguments exist. First, in real-life adherence to all above treatments is very low, leading to a major increase in the incidence and risk of cardiovascular outcomes. Second, although a large number of factors are involved, adherence is adversely affected by the complexity of the prescribed treatment regimen and can be considerably improved by treatment simplification. Third, recent studies in patients with a history of manifest cardiovascular disease have documented that different cardiovascular drugs can be combined in a single tablet with no loss of their individual efficacy or unexpected inconveniences and this does favour adherence to treatment and multiple risk factor control, supporting use of the polypill in secondary cardiovascular prevention. It is finally also mentioned, however, that the polypill may have some drawbacks and that at present no evidence is available that this approach reduces cardiovascular outcome to a greater degree than standard treatment strategies. Trials are under way to provide an answer to this question and thus allow the therapeutic value of this approach to be known.